Queer youth and mental health: What do educators need to know?. Issue 1 (2nd January 2017) - Bryan, Audrey
Abstract : This paper considers the educational implications of the recent emphasis on the mental health and well-being of lesbian, gay, bisexual, transgender, questioning/queer (LGBTQ) people in Ireland. Operating from the perspective that discourses constitute rather than merely reflect material reality, thereby shaping or 'structuring' how we think about, and act, in relation to queer experience, the paper critically engages with discourses which position LGBTQ youth as universally at risk of mental health difficulties, including self-harm and suicidality. It also challenges the corresponding preoccupation with homophobic bullying as the primary lens through which queer experience is understood and addressed in schools, arguing that more space needs to be devoted to other, less harrowing narratives of LGBTQ experience and identity. It highlights some of the more problematic effects of LGBTQ mental health research which frame LGBTQ experience primarily in terms of vulnerability and victimhood and makes the case for a more expansive engagement with LGBTQ identities. The article illuminates the potential that after-queer scholarship holds for a re-imagining of queer youth, sexuality and gender within educational and social research, curriculum materials and educational institutions more generally and concludes with a consideration of specific knowledge and skills that educators should be equipped with in order to disrupt normative understandings of gender and sexuality.